Rancang Bangun Sistem Fuzzy Logic Pada Pengendalian Suhu Dan Kelembaban Inkubator Bayi - Pambudi, Haris Rizal; Widhiada, W.; Adnyana, W. Bandem (Teknik Desain Mekanika, 2022)
Abstract Gestational age is something that can influence the endurance of the embryo and its personal satisfaction. By and large, a pregnancy that is thought of as adequate assuming it keeps going between 37-41 weeks is determined from the main day of the keep going feminine period on the 28th day of the cycle. Meanwhile, if the delivery occurs before the gestational age reaches 37 weeks, the delivery is called premature. Thus, untimely children should be dealt with appropriately so their personal satisfaction can be more ideal. We need infant incubator to control the stability of temperature and humidity. To control temperature and mugginess in inkubator required Arduino Mega 2560 microcontroller, Arduino Uno, LM35 sensor, DHT22 sensor and added fuzzyylogic.. Using temperature parameters with a set point of 36ºC and humidity with an RH range of 60-80%. With the target temperature signal error on the system ?5% and the maximum system overshoot temperature ?5%. The results of this study obtainedaan average signal error = 0.135% and a maximum overshoot = 0.834% in the no-load test. The average signal error = 1.757% and maximum overshoot = 1.052% in the test with a load of 2 Kg. Keyword: Prematur Baby, Infant Incubator, Temperature Control, Fuzzy logic